2006
DOI: 10.4049/jimmunol.176.9.5321
|View full text |Cite
|
Sign up to set email alerts
|

CD72 Down-Modulates BCR-Induced Signal Transduction and Diminishes Survival in Primary Mature B Lymphocytes

Abstract: CD72, a 45-kDa type II transmembrane glycoprotein carrying an ITIM motif, is believed to be an inhibitory coreceptor of the BCR. Mature B cells lacking CD72 show enhanced Ca2+ mobilization and are hyperproliferative in response to BCR ligation. However, the signal transduction pathways downstream of BCR signaling that transmit the inhibitory effect of CD72 in mature B cells remain unknown. To address this question, we used hen egg lysozyme-specific BCR transgenic mice to elucidate the differential cell signali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
29
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 36 publications
1
29
0
Order By: Relevance
“…In agreement with these results, SHP-1 has been found constitutively associated with the BCR complex and plays an inhibitory role in B cell signaling through ITIM-bearing inhibitory coreceptors [15,16]. For example, CD22, Fc␥RII2B1, and CD72 may negatively regulate BCR signaling through recruitment of SHP-1 in human [17,18] and in murine B cells [19,20], respectively.…”
Section: Introductionsupporting
confidence: 53%
“…In agreement with these results, SHP-1 has been found constitutively associated with the BCR complex and plays an inhibitory role in B cell signaling through ITIM-bearing inhibitory coreceptors [15,16]. For example, CD22, Fc␥RII2B1, and CD72 may negatively regulate BCR signaling through recruitment of SHP-1 in human [17,18] and in murine B cells [19,20], respectively.…”
Section: Introductionsupporting
confidence: 53%
“…4A, 4B). However, a previous study demonstrated that BCR ligationinduced calcium response is enhanced in Cd72 2/2 B cells (15,16). Thus, CD72-mediated regulation of BCR signaling depends on experimental conditions.…”
Section: Discussionmentioning
confidence: 97%
“…It is already well established that CD72 is a negative regulator of BCR signaling (12)(13)(14)(15)(16). Expression of CD72 a negatively regulates both calcium signaling and ERK phosphorylation induced by BCR ligation in BAL17 cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Signaling through the BCR on B-cells can be regulated by the inhibitory receptor FcγRIIb [9,10]. FcγRIIb belongs to the low affinity FcγRII (CD32) family, which comprises three isoforms with highly homologous structure but opposing functions.…”
Section: Introductionmentioning
confidence: 99%